Back to Basics: Guideline Review and Commenting. (26th October 2015) - Conner, Ramona L.; Spruce, Lisa; Hicks, Rodney W.
Abstract: Professional guidelines are based on evidence. AORN develops the Guidelines for Perioperative Practice based on a review of pertinent evidence; however, perioperative nurses should participate in the review and public commenting process for these practice guidelines. This article explains how nurses can participate to strengthen the guidelines and help make them accurate and applicable to perioperative practice.